2012
DOI: 10.1371/journal.pone.0036369
|View full text |Cite
|
Sign up to set email alerts
|

Pokeweed Antiviral Protein Increases HIV-1 Particle Infectivity by Activating the Cellular Mitogen Activated Protein Kinase Pathway

Abstract: Pokeweed antiviral protein (PAP) is a plant-derived N-glycosidase that exhibits antiviral activity against several viruses. The enzyme removes purine bases from the messenger RNAs of the retroviruses Human immunodeficiency virus-1 and Human T-cell leukemia virus-1. This depurination reduces viral protein synthesis by stalling elongating ribosomes at nucleotides with a missing base. Here, we transiently expressed PAP in cells with a proviral clone of HIV-1 to examine the effect of the protein on virus productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…1B). This decrease agreed with our previous p24 ELISA results illustrating a 450-fold reduction in virus production from cells expressing PAP (Mansouri et al 2012). To test whether the antiviral effect of PAP was due to cellular toxicity, cells were metabolically radiolabeled with […”
Section: Expression Of Pap Decreases Hiv-1 Protein Expression Withoutsupporting
confidence: 88%
See 1 more Smart Citation
“…1B). This decrease agreed with our previous p24 ELISA results illustrating a 450-fold reduction in virus production from cells expressing PAP (Mansouri et al 2012). To test whether the antiviral effect of PAP was due to cellular toxicity, cells were metabolically radiolabeled with […”
Section: Expression Of Pap Decreases Hiv-1 Protein Expression Withoutsupporting
confidence: 88%
“…PAP expression in 293T cells results in 17% depurination of rRNA (Chan Tung et al 2008), and consistent with previous results, metabolic labeling of cells showed that this level of depurination is not sufficient to decrease the cellular translation rate (Mansouri et al 2009). We appreciate that our current study was conducted in a cell line and our future work needs to be confirmed in primary cells over a longer time frame; however, we and others have shown previously that expression or application of PAP is not toxic to cells more relevant to HIV-1 infection, such as MT-2, a lymphoblastoid T cell line, and CD4+ T cells (Zarling et al 1990;Mansouri et al 2012). Therefore, we suggest that changes in HIV-1 translation would not be due to a ribotoxic effect of PAP, but rather due to a more specific targeting of viral translation caused by damage to viral RNA.…”
Section: Discussionmentioning
confidence: 95%
“…Much of the recent scientific literature on pokeweed has focused on the plant’s medicinal and antiviral properties, and not its management as a weed in field crops (Baldwin et al 2009; Domashevskiy et al 2012; Maness et al 2012; Mansouri et al 2012). Most of the available literature on pokeweed as a weed is in non–peer-reviewed research reports and conference proceedings.…”
mentioning
confidence: 99%
“…Depurination of HIV-1 RNA long terminal repeats may hinder HIV integration [30]. However, RIPs can also activate the host MAP kinase pathway to counter this and increase infectivity [31]. VT has been shown to activate this pathway [32].…”
Section: Resultsmentioning
confidence: 99%